2011
DOI: 10.1038/cdd.2011.164
|View full text |Cite
|
Sign up to set email alerts
|

Many stimuli pull the necrotic trigger, an overview

Abstract: The lab of Jürg Tschopp was the first to report on the crucial role of receptor-interacting protein kinase 1 (RIPK1) in caspase-independent cell death. Because of this pioneer finding, regulated necrosis and in particular RIPK1/RIPK3 kinase-mediated necrosis, referred to as necroptosis, has become an intensively studied form of regulated cell death. Although necrosis was identified initially as a backup cell death program when apoptosis is blocked, it is now recognized as a cellular defense mechanism against v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
336
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(343 citation statements)
references
References 168 publications
(313 reference statements)
4
336
1
2
Order By: Relevance
“…It has been shown that necroptosis is induced by ligand binding to TNF family death domain receptors, pattern recognition receptors, or virus sensors 53. Yet, our data suggest that neither TNFα nor other soluble factors are involved in sCD74/MIF‐induced necroptosis of cardiac myofibroblasts.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…It has been shown that necroptosis is induced by ligand binding to TNF family death domain receptors, pattern recognition receptors, or virus sensors 53. Yet, our data suggest that neither TNFα nor other soluble factors are involved in sCD74/MIF‐induced necroptosis of cardiac myofibroblasts.…”
Section: Discussioncontrasting
confidence: 56%
“…The lack of proteolytic activity of caspase‐8 allows autophosphorylation of RIP1 and subsequent RIP3 and mixed lineage kinase domain‐like pseudokinase (MLKL) activation. Both phospho‐RIP3 and phospho‐MLKL assemble in so‐called necrosomes to trigger cell death 53. We assessed RIP3 activity by Western blot 10 hours after incubation with sCD74/rMIF and observed a 2‐fold increase of RIP3 phosphorylation compared with untreated control (control versus sCD74/rMIF: 100% versus 222.2±45.98%; P =0.0376, d =1.88), whereas neither rMIF nor sCD74 treatment alone affected phospho‐RIP3 levels (Figure 2C and 2D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising, because TNFinduced necroptosis is frequently considered to be more pro-inflammatory than TNF-initiated outcomes that occur in the presence of caspase activity. 22,[27][28][29] This view appears to be predicated upon the notion that TNF promotes either apoptosis or necrosis, with the latter typically being proinflammatory and the former not. However, because TNF is itself highly pro-inflammatory as illustrated above (Figures 1a and b), the impact of necroptosis on TNF-induced inflammatory events remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…RIPK1 is known to act in both caspase-dependent (apoptotic) and RIPK3-MLKL-dependent (necroptotic) death pathways. 32 To confirm which effectors were required downstream of RIPK1 for each death mechanism, we expressed RIPK1 gyrase in either WT MEFs or those lacking components of the death pathways. When RIPK1 gyrase was induced and dimerized in various lines of MEFs (Figure 3a), death occurred, except in the caspase 8 À / À line that also lacked RIPK3 (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%